Pain management approach in a cat with feline arterial thromboembolism assessed using the Feline Grimace Scale - Andadari, Afifah Yudining Dwi; Napitu , Napitu; Herawati , Herawati (ARSHI Veterinary Letters, 2025)
Feline arterial thromboembolism (FATE) is a life-threatening condition characterized by partial or complete arterial obstruction due to thrombus formation, most commonly secondary to hypertrophic cardiomyopathy (HCM). The resulting ischemia causes severe pain, which is often overlooked in clinical practice. The Feline Grimace Scale (FGS) provides a rapid and objective tool for pain assessment in cats. This report describes an adult female cat presenting with left hindlimb paresis, cyanosis, and femoral pulse deficit, with an initial FGS score of 6/10. Blood chemistry showed elevated creatine kinase (CK) levels, and echocardiography confirmed reduced femoral arterial flow and myocardial hypertrophy, consistent with HCM. A multimodal management approach was applied, including gabapentin, tramadol, clopidogrel, furosemide, and heparin therapy. Despite treatment, the affected limb developed gangrene, necessitating amputation. Preoperative analgesia consisted of pethidine, ketamine, and xylazine, followed by regional lidocaine nerve blocks and postoperative fentanyl continuous rate infusion. The surgical site healed completely within 21 days, and over a four-month follow-up period, the FGS score improved from 9 to 0, indicating complete pain resolution.